2002
DOI: 10.1016/s0969-2126(02)00803-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA Complexed Structure of the Key Transcription Factor Initiating Development in Sporulating Bacteria

Abstract: Sporulation in Bacillus species, the ultimate bacterial adaptive response, requires the precisely coordinated expression of a complex genetic pathway, and is initiated through the accumulation of the phosphorylated form of Spo0A, a pleiotropic response regulator transcription factor. Spo0A controls the transcription of several hundred genes in all spore-forming Bacilli including genes for sporulation and toxin regulation in pathogens such as Bacillus anthracis. The crystal structure of the effector domain of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
90
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 38 publications
1
90
0
1
Order By: Relevance
“…In the DNA-binding domain all of the residues known to make contact with the DNA target of Spo0A, the 0A box, are identical, which suggests that the sequence of the 0A box is invariant in sporulating bacteria (39). Amino acid sequence conservation is also apparent in the Spo0F and Spo0B components of the phosphorelay (33).…”
mentioning
confidence: 99%
“…In the DNA-binding domain all of the residues known to make contact with the DNA target of Spo0A, the 0A box, are identical, which suggests that the sequence of the 0A box is invariant in sporulating bacteria (39). Amino acid sequence conservation is also apparent in the Spo0F and Spo0B components of the phosphorelay (33).…”
mentioning
confidence: 99%
“…The target sites reveal a consensus binding sequence, TTTGTCRAA, which is known as the 0A box (23). The crystal structure of the C-terminal (DNA-binding) domain of the Bacillus stearothermophilus ortholog in a complex with 0A box sequences has been solved (32). This structure reveals contacts of the DNA-binding domain with bases in the 0A box and with the DNA backbone and has led to the suggestion that Spo0AϳP dimers are capable of forming tandem arrays in a head-to-tail arrangement along the DNA (32).…”
mentioning
confidence: 99%
“…The crystal structure of the C-terminal (DNA-binding) domain of the Bacillus stearothermophilus ortholog in a complex with 0A box sequences has been solved (32). This structure reveals contacts of the DNA-binding domain with bases in the 0A box and with the DNA backbone and has led to the suggestion that Spo0AϳP dimers are capable of forming tandem arrays in a head-to-tail arrangement along the DNA (32). It was suggested that such arrays may form in the regulatory region for genes such as spoIIA, spoIIE, and spoIIG that exhibit multiple 0A boxes in tandem extending far upstream from the start site of transcription.…”
mentioning
confidence: 99%
“…Our nuclear magnetic resonance (NMR) structure of Spo0F with John Cavanagh defined the flexible regions found in conformers that we proposed to be the regions responsible for interaction with other proteins of the phosphorelay (12). Moreover, we captured the structure of Spo0A bound to its DNA target, in a crystal, allowing determination of residues important for binding (101).…”
Section: Understanding Molecular Recognition By Protein Structure Andmentioning
confidence: 99%